Amphoteric starch derivatives as reusable flocculant for heavy-metal removal. Issue 3 (3rd January 2018) - Wu, Liang; Zhang, Xingrong; Chen, Long; Zhang, Huan; Li, Chengbi; Lv, Yin; Xu, Yisheng; Jia, Xin; Shi, Yulin; Guo, Xuhong
Abstract : A pH-responsive starch-based flocculants containing both cationic and anionic functional groups has been developed. The saturated flocculant can be facilely regenerated and separated from the solution by applying an external pH stimulus. Abstract : A pH-responsive amphoteric starch derivative (PRAS) bearing dual functional groups (amino and carboxyl groups) was prepared through etherification of starch with 2-chloro-4, 6-diglycino-[1, 3, 5]-triazine. PRAS exhibits a reversible pH-response property in aqueous solution. The attractive property of PRAS is that it could be used as an effective flocculant for heavy metal-ion ( e.g. Cu(ii ) and Zn(ii )) removal from wastewater by changing pH. The transition of hydrophobicity–hydrophilicity would produce shrinkage of the polymer matrix, facilitating the release of heavy-metal ions from the saturated flocculant. As an ideal flocculant PRAS displayed outstanding stability and reproducibility, whose remove rate for Cu(ii ) and Zn(ii ) remained at 93% and 91% after three flocculation/regeneration cycles.